Forgiveness and Restorative Justice Perspectives from Christian Theology - Blyth, Myra N.; Mills, Matthew J.; Taylor, Michael H. (Cham Springer International Publishing, 2021)
1. Introduction -- 2. Rituals of Restoration -- 3. Reframing the Narrative of Victimhood -- 4. The Role and Meaning of Forgiveness -- 5. Just Enough to Be Satisfied -- 6. Forgiveness and the Conference Experience -- 7. Restorative Justice and Social Justice -- 8. Forgiving in the Presence of God -- 9. Conclusion.
The meaning of ‘forgiveness’ and its role within restorative justice are highly contested. This book offers analysis from practical and academic perspectives within Christian theology, against a rich canvas of related concepts, including victimhood, sin, love, and vulnerability. Critical friends of restorative justice, the authors argue that forgiveness – whether as journey or act, unilateral or mutual, conditional or unconditional – is necessary to achieving a fully restorative resolution to acts of harm. They also suggest that Christianity, with its meaning-giving metanarrative of restoration, and preference for communitarian approaches to justice, may have epistemic value for evaluating and even deepening the theory and practice of restorative justice.
Keywords: Theology; Social Justice; Human Rights; Corrections; Punishment; Aufsatzsammlung